The Role of Principal’s Managerial Leadership through Management based on School in Improving Quality of Students at Dwi Warna Senior High School Medan - Sabar Lamhot Tua Simatupang; Rosma Nababan; Sanhedrin Ginting (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims: (a) to investigate the principal's planning process in implementing school-based management at Senior High School of Dwi Warna Medan, b) to investigate the principal's implementation strategy in implementing school-based management in Dwi  Warna Medan High School, and (c) to know the form of supervision and evaluation of the principal in the application of school-based management at  Senior High School of Dwi Warna  Medan. The type of this research is field research by using qualitative methods and descriptive approach. Data collection is conducted through interviews, observations and documentation in the field by involving principals and other school residents. The results of the research indicate that: (a) The process of planning the implementation of school- based management at  Senior High School of Dwi Warna runs pretty well and is implemented by involving the committee and all other school components; (b) The principal's implementation strategy in implementing school-based management is quite well implemented, this is proven by involving all components of the school, and (c) The form of supervision and evaluation of school-based management implementation at  Senior High School of Dwi Warna runs quite well. This is evidenced by the two supervision techniques that are carried out regularly by the principal. The evaluation not only emphasizes the process of teaching and learning activities, but also considers the other necessary aspects, for example: the competence of educators, students,  infrastructure, finance and community relations.